The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1745-6584.2007.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Infiltration and Impacts of Introduced Water Using Strontium Isotopes

Abstract: Water introduced to surface drainages, such as agricultural and roadway runoff, mine drainage, or coalbed natural gas (CBNG)-produced water, potentially can be of environmental concern. In order to mitigate potential environmental effects, it may be important to be able to trace water discharged to the surface as it infiltrates and interacts with near-surface aquifers. We have chosen to study water withdrawn during CBNG production for isotope tracing in the hyporheic zone because it poses a variety of economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
(50 reference statements)
0
33
0
Order By: Relevance
“…The distinct elemental composition and isotopic signatures of produced water provide unique opportunities for tracer studies that could indicate aquatic system exposure. Stable isotopes of strontium and carbon have been used to trace water from coalbed natural gas production wells to surface waters and hyporheic zones (Brinck and Frost 2007). Osborn et al .…”
Section: Challenges and Potential For New Researchmentioning
confidence: 99%
“…The distinct elemental composition and isotopic signatures of produced water provide unique opportunities for tracer studies that could indicate aquatic system exposure. Stable isotopes of strontium and carbon have been used to trace water from coalbed natural gas production wells to surface waters and hyporheic zones (Brinck and Frost 2007). Osborn et al .…”
Section: Challenges and Potential For New Researchmentioning
confidence: 99%
“…The second is used to estimate the CBNG end-member values based on measurements made along Beaver Creek, a tributary of the Powder River that is known to contain large amounts of CBNG produced water (Wyoming Department of Environmental Quality (WDEQ), 2006,2008). Beaver Creek water is known to represent CBNG produced water because the Sr and C isotopic composition of Beaver Creek water is within the range of 87 Sr/ 86 Sr ratios and d 13 C DIC of CBNG-produced water collected directly from wellheads (Frost et al, 2002;Brinck and Frost, 2007;Sharma and Frost, 2008). The third incorporates a four end-member mixing model to determine the contributions of the four different sources (i.e.…”
Section: Likelihood Of Isotope Ratio and Concentration Datamentioning
confidence: 99%
“…Because of the paucity of gauging stations on the Powder River (five stations; Clark et al ., ), uncertainties in water volumes carried by tributaries, and conveyance loss in holding ponds and infiltration, simple volumetric calculations to determine the proportion of CBNG produced water are not possible. The few studies that have been conducted to evaluate how much infiltration and conveyance loss occurs from the impoundments and ponds that hold CBNG produced water have shown that these quantities are very difficult to estimate, in part because they are temporally (seasonally) dynamic (Brink and Frost, ; Payne and Saffer, ; Wheaton and Brown, ). Two studies, however, examined historical water quality data from the Powder River to determine whether there were changes that may be attributed to development of CBNG activity in the PRB.…”
Section: Introductionmentioning
confidence: 99%
“…Originally the strontium isotope ratio was used only in geological and archeological sciences [7, 8], but recently it has also been used in hydrology and studies of subsurface water behavior [9, 10]. The study of Voerkelius et al [11] shows the change in the 87 Sr/ 86 Sr isotopic ratio in natural mineral water extracted in Europe.…”
Section: Introductionmentioning
confidence: 99%